Lumbar Epidural Contrast Spread Patterns for the Interlaminar Approach: Three-Dimensional Analysis Using Antero-Posterior, Lateral, and Contralateral Oblique Views. Issue 4 (14th October 2019) - Gill, Jatinder; Simopoulos, Thomas; Orhurhu, Vwaire; Nagda, Jyotsna; Aner, Moris
Abstract: Objective: To describe and analyze lumbar epidural contrast spread patterns in antero-posterior (AP), lateral, and contralateral oblique (CLO) views. Methods: Lumbar epidural contrast spread patterns after interlaminar injection were prospectively collected in AP, lateral, and several CLO views and analyzed for multiple variables; three-dimensional mapping was also performed. Results: Epidural contrast patterns were prospectively analyzed in 28 subjects. The median volume of contrast injected was 2 mL; the AP view was more sensitive than the lateral view to detect foraminal uptake (13/28, 46%, 95% confidence interval [CI] = 27–66%, vs 7/28, 25%, 95% CI = 11–45% subjects). CLO view demonstrated the most consistent location for epidural contrast spread, with contrast contacting the ventral laminar margin in 28/28 (100%, 95% CI = 87–100%) patients. The most common location of contrast spread in the lateral view was at the facet joint lucency, with only 8/28 (29%, 95% CI = 13%–49%) subjects showing contrast contacting the spinolaminar junction. Lateral view was more sensitive than the CLO view in ventral epidural contrast spread detection. The extent and distribution of the spread did not bear any relationship to the volume injected or to the needle location in AP view. Conclusions: CLO view provides the most consistent landmark for lumbar epidural contrast spread, and lateral view is most suited to confirming ventral epidural spread. The AP view may be the most optimal for determining target access when considering access to the dorsal root ganglia; in an individual patient, the volume injected and needle location in AP view do not reliably predict target access. The volume to be injected and the need to re-access or obtain multisite access must be prospectively determined, based upon observation of the spread.